PENGGUNAAN SEJARAH LISAN DALAM HISTORIOGRAFI INDONESIA - Erman, Erwiza (Jurnal Masyarakat dan Budaya, 2011)
The professional historians tend to gather information more on the sources of archives and other documentary materials than unwritten sources through interviews. However, since the emergence of oral history in the 19th century in the West, the ongoing debates have been occurring between the pros and the cons with the use of oral sources for writing history. Nevertheless, the oral history activity continues, beginning from its focus on elite experience as found in the United States in 1948, to the experience of ordinary people in Britain in the 1950s and 1960s. Advances in recording technology and new approaches of other social disciplines such as antropology and sociology to oral history, have given a broad influence on historians in third world countries, including Indonesia. Gathering information from oral history, new data found and new historical analysis can be made. This paper tries to see the use and development of oral history in Indonesia. The first section will map the development of Indonesian historiography very briefly and the problem of sources. The next section focuses on the development of oral history in the West and then its influence in Indonesia. The third section describes the use of oral history and its approach, and finally concludes with some closing notes.Keywords: Indonesian historiography, oral history, object, context.